Structure identification of soybean peptides and their immunomodulatory activity. (15th October 2021) - Wen, Lingrong; Jiang, Yueming; Zhou, Xuesong; Bi, Huimin; Yang, Bao
Highlights: Fifty-one soybean peptides were identified by UPLC-MS/MS. There were forty-six immunomodulatory peptides. Soybean peptides could increase iNOS expression. The release of cytokines IL-6 and TNF-α was elevated. Abstract: Soybean peptides are functional food with good health benefits. The health benefits presented are highly dependent on the peptide structure. In this work, soybean peptides were prepared by alkaline protease hydrolysis of soybean proteins. The peptide structure was identified by UPLC-MS/MS. The full peptide composition was revealed. The sequences of 51 peptides were identified and 46 peptides were assigned as immunomodulatory peptides. By evaluating the immumonodulatory activity and mechanism, soybean peptides could facilitate the proliferation of macrophages. The pinocytotic activity and NO level were increased. Induction of iNOS mRNA expression by soybean peptides was responsible for the increased NO production. The release of cytokines IL-6 and TNF-α was elevated and their levels were equal to positive control. The mRNA expression levels of IL-6 and TNF-α were also improved by soybean peptides, but much lower than positive control. The results were helpful for application of soybean peptides in functional foods.